Assessing of Biology Test Question Quality Using Anates Software - Siti Mutmainah; Rufi’I (STAI Miftahul Ula Nganjuk, 2024)
This research uses a quantitative descriptive approach. This research aims to determine the quality and appropriateness of Class XI Biology question items consisting of validity, reliability, level of difficulty, distinguishing power and distractor quality. The subjects are SMA N 1 Driyorejo Gresik as many as 30 students. Data collection in this research was carried out through student answer sheets, then the data was processed using Anates Ver 4.0.9. The test results show that the questions are appropriate and of good quality with a correlation of 0.62 and a reality coefficient of 0.76. This resulted in the question criteria being declared as having high validity, with four levels of difficulty and a small number of the quality of the distractor has poor quality test items.